Isolated aplasia of submandibular salivary gland and contralateral prominence of submandibular and sublingual salivary glands incidentally found on 68Ga-prostate-specific membrane antigen positron emission tomography—computed tomography - Yousefi-Koma, Abbas; Ahmadi, Reyhane; Gorzi, Saba; Shiravand, Yaser; Qutbi, Mohsen (World Journal of Nuclear Medicine, 2020)
Prostate-specific membrane antigen (PSMA)-targeted imaging is now an effective tool for the evaluation of prostate cancer patients. Although salivary glands take up 68Ga-PSMA avidly, pathologies of these glands may be readily noticeable. Herein, we present a case of prostate cancer referred for 68Ga-PSMA positron emission tomography—computed tomography in whom an isolated aplasia of the submandibular salivary gland was incidentally found.
Keywords: 68Ga-prostate-specific membrane antigen positron emission tomography—computed tomography; isolated aplasia; submandibular salivary gland